Characteristics and experiences of buprenorphine-naloxone use among polysubstance users. (2nd November 2018) - Walker, Robert; Logan, TK; Chipley, Quintin T.; Miller, Jaime
ABSTRACT: Background : With a rise in overdoses and medical emergencies related to opioids, buprenorphine-naloxone (bup-nx) is seen as a preferred treatment for opioid dependence. However, the research examining experiences with bup-nx among polysubstance users who may or may not be opioid dependent has been limited. Objectives : The purpose of the study was to examine use, characteristics of users, and experiences of bup-nx use among polysubstance users entering drug-free recovery programs. Methods : This study examined secondary data on 896 opioid or opiate user individuals (53.4% male) collected by drug-free, self-help-based residential recovery centers during intake. Results : One-quarter of users said bup-nx helped them with their substance use while 75% of bup-nx users reported that bup-nx either had no effect or a negative effect on their drug problems. Of the very few (4%-7%) obtaining bup-nx solely through a prescription, over 90% reported relief from withdrawal. However, over 80% of those who obtained bup-nx through illicit means reported using bup-nx until their preferred drug could be obtained and used it for its euphoriant effect. Three groups of opioid users were created including one group with no bup-nx use, one with lifetime but not recent bup-nx use, and one with recent (past 6 month) use. There were differences in substance use patterns and characteristics of bup-nx experiences between the different groups. Conclusions : Results suggest that the views of bup-nx by individuals in drug-free recovery centers are varied, with many seeing bup-nx as not unlike other opioids while others report bup-nx as self-medication.